Financial imbalances and medium-term growth-at-risk in Norway - Elif C. Arbatli-Saxegaard; Karsten R. Gerdrup; Rønnaug M. Johansen (Norges Bank, 2020)
We examine how measures of financial imbalances affect macroeconomic tail risks over the medium-term in Norway and in other advanced economies. We use a broad set of financial indicators to capture cyclical systemic risk in the financial system and different quantile regression models to characterise their effects on the medium-term growth distribution. We find that an increase in financial indicators is associated with both a more adverse prediction for growth-at-risk (5th percentile of growth distribution) and higher downside risks to growth (difference between the median and the 5th percentile of growth distribution). Among financial indicators, credit growth has the most significant effect on downside risks to growth. We also find that downside risks are higher under a fixed exchange rate regime. Using our estimates, we focus on two policy-relevant applications. First, we summarise how financial indicators and growth-at-risk have evolved over time in Norway and how this framework can be used to quantify and communicate risks to the economic outlook. Second, we show how this framework can be used to calibrate the severity of cyclical stress test scenarios.
hdl:11250/2659923
Keywords: E44; G01; G10; 330; Financial stability; growth-at-risk; quantile regressions